Improvement Of The Design Of The Saw-Cutting Machine (Texas Journal of Engineering and Technology, 2024)
This article presents the schemes and the technological process of the pilon-cutting machine for cutting saws for gins and linters designed to simplify the design of the pilon-cutting machine and improve the accuracy of cutting saws